Parental involvement : its relationship with literacy development of kindergarten pupils in Urbiztondo, Division I of Pangasinan - Daquera, Jenny Rose R. (Pangasinan : [s.n.], 2017)
The study aimed to determine the relationship between the parental involvement with the literacy development of the kindergarten pupils in Urbiztondo, Pangasinan during the school year 2016-2017. Descriptive correlation research design was used and questionnaire checklist as a data gathering tool. The respondents of the study consisted of 583 parents and 13 kindergarten teachers from 11 public schools.
Bibliography: pages 54-59.
CHED-La Union
Keywords: Parent-child relationship